2014
DOI: 10.1016/j.aquaculture.2014.02.033
|View full text |Cite
|
Sign up to set email alerts
|

Effective use of microbial biomass products to facilitate the complete replacement of fishery resources in diets for the black tiger shrimp, Penaeus monodon

Abstract: A series of experiments were conducted with black tiger shrimp (Penaeus monodon) juveniles to firstly determine the effects of reducing fishmeal inclusion in a diet and then to evaluate the potential for a microbial bioactive to support complete replacement of both fishmeal and fish oil in feeds when fed under clear-water and green-water conditions. The isoproteic and isoenergetic replacement of fishmeal resulted in a consistent decline in growth performance indicating that at every decrease in fishmeal below … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
48
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 29 publications
(19 reference statements)
4
48
1
Order By: Relevance
“…It is important to consider that the higher growth rate elicited by diet 95FM/5SC cannot be attributed only to the dietary nitrogen supplied by SC, but also to a potential effect of the microalgae promoting the efficient use of other nutrients supplied by FM. The latter effect has been proposed by Glencross et al (2014) after using low levels of microbial biomass in aquaculture diets. Diet 90FM/10GR supplied higher amounts of dietary nitrogen than the other mixed diets although in similar proportions than those established in the formulated diets.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…It is important to consider that the higher growth rate elicited by diet 95FM/5SC cannot be attributed only to the dietary nitrogen supplied by SC, but also to a potential effect of the microalgae promoting the efficient use of other nutrients supplied by FM. The latter effect has been proposed by Glencross et al (2014) after using low levels of microbial biomass in aquaculture diets. Diet 90FM/10GR supplied higher amounts of dietary nitrogen than the other mixed diets although in similar proportions than those established in the formulated diets.…”
Section: Discussionmentioning
confidence: 96%
“…In the present study, it was observed that addition of 5 and 10% of the microalgal biomass of both species elicited similar or higher growth as the use of FM alone. Glencross et al (2014) recently reported that even small dietary levels of microbial biomass (in this case bacterial) frequently cause positive results in terms of shrimp growth and survival. Authors consider that the microbial biomass contains molecules that facilitate the physiological use of other nutrients.…”
Section: Discussionmentioning
confidence: 99%
“…The growth promoting effects of MB on shrimp have been reported in a number of studies (Burford et al, 2004;Glencross et al, 2013;Glencross et al, 2014;Glencross et al, 2015;Kuhn et al, 2008;Kuhn et al, 2009). Nutritional studies have demonstrated that the growth enhancing effects of bioactive products derived from MB are critically dependent on meeting the overall nutritional demands of shrimp (Glencross et al, 2013;Glencross et al, 2014).…”
Section: Introductionmentioning
confidence: 97%
“…These include superior growth and feed utilization (Glencross et al, 2013;Glencross et al, 2014), increased harvest yields (Preston et al, 2009) and increased viral tolerance (Sellars et al, 2015). Despite these improvements, the reproductive performance of domesticated broodstock remains inferior when compared with wild-caught broodstock Coman et al, 2006;Menasveta et al, 1993;Peixoto et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation